Perbaikan Proses Pencatatan Kehadiran Karyawan yang Berdampak pada Pembayaran Tunjangan/Upah di PT. X - William Hansel Trisila; Debora Anne Yang Aysia (Jurnal Titra, 2019)
PT. X is a multinational company that produces consumer goods and has mastered that consumer goods market in Indonesia. PT. X has 28.212 employees and each employee must be aware of their rights and responsibilities. PT. X has desired to digitalize processes that related to employee rights and responsibilities, one of which is the employee attendance recording process. Attendance recording process must have a standard process to support the digitalization process. Employee attendance recording process at PT. X consists of three parts, pre-attendance process, attendance process, and attendance claim process. All of three processes have their own problems and need to be corrected. Problems collection is done by observing and interviewing employees who carry out the process of recording employees. Improvement of employee attendance recording process was analyzed with fishbone diagrams and brainstorming tools. The improvement processes that have been analyzed will be validated to the management at PT. X so the improvement processes won’t cause disruption to the course of business processes at PT. X. Process improvement resulted savings equal to 8 working hours and saving in supervisor equal to 7 working hours, who could be allocated to other processes needed by the company.